EX-TERRORISTS REINTEGRATION PROGRAMS ON CONDITIONAL RELEASE PERIOD BY FORMERS FOUNDATION YAYASAN LINGKAR PERDAMAIAN (YLP) - Masithoh, Nidia; Priyanto, Sapto; Syauqillah, Muhammad (UI Scholars Hub, 2022)
Ex-terrorist reintegration must be carried out in an integrated way from in-prison empowerments with post-release program initiatives. The involvement of formers in reintegration has received considerable attention in recent years. The involvement of formers foundations in the assistance and supervision is to build a social support to prevent recidivism. Usually, ex-terrorist experience inherent post-release risks and challenges such as stigmatization, mistrust and socioeconomic exclusions. Transition period is a crucial in determining the success of prevention program. Formers foundation initiates community-based assistance and supervision by encouraging financial independence, changing perspectives towards moderation through discussion and dialogue and ensuring community acceptance in the first place. This study uses a descriptive qualitative method to describe the intervention of formers foundation in reintegration scheme by emphasizing the crucial risks of the transition period. Social Bond Theory is used to find out the elements of preventing ex-terrorist from re-committing terrorism. This research found that Yayasan Lingkar Perdamaian as formers foundation provides assistance on moral and material for ex-terrorist on their conditional release. Yayasan Lingkar Perdamaian also ensures acceptance of community for ex-terrorist reintegration in their area.